Perampanel in real‐world clinical care of patients with epilepsy: Interim analysis of a phase IV study. Issue 1 (19th December 2020) - Wheless, James; Wechsler, Robert T.; Lancman, Marcelo; Aboumatar, Sami; Patten, Anna; Malhotra, Manoj
Abstract: Objective: To assess the retention rate, efficacy, safety, and dosing of perampanel administered to patients with epilepsy during routine clinical care in the retrospective phase IV, PROVE Study (NCT03208660). Methods: Exposure, efficacy, and safety data were obtained from the medical records of patients initiating perampanel after January 1, 2014, across 29 US study sites. The cutoff date for this interim analysis was October 10, 2018. The primary efficacy endpoint was retention rate. Secondary efficacy endpoints included median percent changes in seizure frequency, seizure‐freedom rate, and overall investigator impression of seizure effect. Results: All enrolled patients (N = 1121) received perampanel. Mean (standard deviation [SD]) cumulative duration of exposure to perampanel was 16.6 (14.7) months; overall mean (SD) daily perampanel dose was 5.7 (2.7) mg. Perampanel uptitration occurred weekly (21.1%), biweekly (23.8%), every 3 weeks (1.5%), other (43.3%), and unknown (10.3%). Across the Safety Analysis Set (N = 1121), retention rate on perampanel at 24 months was 49.5% (n = 319/645). At 12 months, the median reduction in seizure frequency per 28 days from baseline in the small number of patients for whom data were available was 75.0% (n = 85), and 30/85 (35.3%) patients were seizure free. Based on investigator impression at the end of treatment, improvement, no change (ie, stable), or worsening of seizures was reported in 54.3%, 33.7%, and 12.0% of patients, respectively. Treatment‐emergent adverse events occurred in 500 (44.6%) patients; the most common were dizziness (9.2%), aggression (5.4%), and irritability (4.5%). Serious treatment‐emergent adverse events occurred in 32 (2.9%) patients. Significance: Favorable retention and sustained efficacy were demonstrated for ≥12 months following initiation of perampanel during routine clinical care in patients with epilepsy.